MAKNA PASAL 33 UNDANG-UNDANG DASAR 1945 DALAM PEMBANGUNAN HUKUM EKONOMI INDONESIA - Elli Ruslina (The Constitutional Court of the Republic of Indonesia, 2016)
Article 33 of the 1945 Constitution serves as the basis for Indonesian Economy. It contains the principle of togetherness and brotherhood. Therefore, in the development of Indonesian Economic Law, Article 33 of the 1945 Constitution is imperative in nature that it is asserted in the laws and regulations concerning the economy, “...it is the prosperity of the society that should be prioritized...not the welfare of individuals”.